The New Method to Determine the Value of Speed Droop for Subcritical Coal Fire Power Plant in Order to Contribute to Primary Frequency Control of Power System. (2017) - Fahmilia; Leksono, Edi
Abstract: Frequency is the controlled variable in balancing electricity supply and demand of power system. Frequency control needs power plants contributions by changing the output power of the corresponding generator until balance condition between electrical supply and demand gets reestablished. The contribution of each power plant is determined by some parameters speed droop and dead band. The Indonesian government regulation for speed droop is a maximum of 5% with dead band 0.03 Hz but not all power plants can set that value. This paper present new method to determine the optimal speed droop by analyzed the energy storage at Suralaya Power Plant unit 5, 6 and 7.